Исламские Религиозные Объединения В Правовом, Политическом И Социальном Контексте России (Islamic Religious Associations In The Legal, Political and Social Context Of Russia) - Maulana, Amy; Yavorsky, Dmitry (Jurnal Cita Hukum, 2020)
Abstract The purpose of this article is to describe and analyze the activities of Islamic spiritual administrations in Russia. The method used in writing this article is a method of descriptive analysis using data from the literature. The results of the study show that the Spiritual administration of Muslims represents the interests of all Muslims in Russia. The spiritual administration of Muslims is increasingly promoting Islamic education in Russia. It represents the rights of Russian Muslims as citizens and helps to overcome religious extremism, terrorism, xenophobia and Islamophobia in Russia. Interaction between Islam and the state has become a priority. For the state, Islam in Russia is a valuable diplomacy abroad. In the future, the role of the spiritual administration of Muslims should be strengthened, strive for unity and cooperation between the Spiritual administration of Muslims, and give priority to the interests of Russian Muslims Keywords: Muslim spiritual administration, Russian Muslims Abstrak Tujuan dari artikel ini adalah untuk menggambarkan dan menganalisis kegiatan administrator spiritual Islam di Rusia. Metode yang digunakan dalam menulis artikel ini adalah metode analisis deskriptif menggunakan data sastra dari literatur. Hasil studi menunjukkan bahwa administrasi Spiritual muslim mewakili kepentingan semua Muslim di Rusia. Administrasi spiritual muslim semakin mempromosikan pendidikan Islam di Rusia. Ini mewakili hak-hak Muslim Rusia sebagai warga negara dan membantu untuk mengatasi ekstremisme religius, terorisme, xenophobia dan Islamophobia di Rusia. Interaksi antara Islam dan negara telah menjadi prioritas. Bagi negara, Islam di Rusia adalah diplomasi berharga di luar negeri. Di masa depan, peran administrasi spiritual muslim harus diperkuat, berusaha untuk kesatuan dan kerjasama antara kelompok Spiritual muslim, dan memberikan prioritas untuk kepentingan Muslim RusiaKata Kunci: Administrasi spiritual Muslim, Muslim Rusia Аннотация Целью данной статьи является описание и анализ деятельности исламских духовных управлений в России. В ходе исследования применялись методы описания и анализа, использовались данные из научной литературы и официальных ресурсов религиозных организаций. Результаты исследования показывают, что система духовных управлений мусульман представляет интересы всех исламских общин России. Духовные управления способствует развитию исламского образования в России. Они представляют права российских мусульман как граждан, а также помогают преодолеть религиозный экстремизм, терроризм, ксенофобию и исламофобию в России. Взаимодействие с исламскими религиозными организациями находится в ряду приоритетных задач Российского государства. Ислам для России -это ценный дипломатический ресурс. Вывод статьи: следует укреплять позиции духовных управлений мусульман в России, стремиться к сотрудничеству между духовными управлениями, учитывать интересы российских мусульман.Клюевые Слова:  Духовное управление мусульман, мусульмане России